An investigation into the commercialisation of initiation schools: A case of Eastern Cape, South Africa - Mdhluli, Tsetselelani D. (HTS teologiese studies, 2021)
This study investigated the commercialisation of initiation schools. It is argued that the economic hardships and lack of employment have led to some people resorting to any way of living merely for financial gain. The specific objectives were to determine and assess the regulations that govern the opening and running of initiation schools and to determine the palliatives that can curb commercialisation of initiation schools. The research was based on sociocultural theory and used a qualitative research design. The data collection methods used included secondary sources, focus group discussions and face-to-face interviews. The outcomes were that initiation schools are open to abuse by opportunistic unemployed people and some who are employed who want to add to their meagre wages so as to make a living, thereby crippling and undermining a cultural practice that is highly esteemed. The study recommends effective indigenous knowledge management to curb the unethical practices of commercialisation of initiation schools. Furthermore, strategies should be adopted to document this knowledge and formulate policies that will govern it.Contribution: In line with the journal scope, this article focuses on the African Tradition Religion practice of initiation schools. This subject matter is multi-disciplinary and it covers how the sacred practice has been defiled through commersialisation and deviation from its original intent.